Perlindungan Hukum Guru dalam Pemberian Sanksi kepada Murid di SD Swasta Bina Bangsa Tanjung Morawa - Suci Maharani; Syahrul Bakti Harahap (Pemuliaan Keadilan, 2026)
This research is motivated by the increasing number of legal cases involving teachers resulting from sanctions imposed on students in elementary schools. Teachers often find themselves in a dilemma between exercising their pedagogical authority to discipline students and the risk of legal action from parents due to differing perceptions. This situation highlights the importance of studying legal protection for teachers without neglecting the protection of children's rights in the educational process. This study aims to analyze the forms of legal protection for teachers at Bina Bangsa Private Elementary School in Tanjung Morawa and to identify the factors causing conflicts between teachers, students, and parents, along with efforts to resolve them. The method used is empirical juridical with a field approach. Data were obtained through interviews, observations, and literature review, then analyzed qualitatively to describe the application of legal protection in practice. The results indicate that legal protection for teachers is regulated normatively in legislation, but its implementation is not yet optimal. Teachers remain vulnerable to legal conflicts due to differing understandings regarding the limits of educational sanctions. Factors contributing to these conflicts include differences in perception, lack of communication, increased public legal awareness, and unclear boundaries between educational sanctions and violence. Therefore, strategic efforts are needed, such as reinforcing school regulations, increasing outreach to parents, strengthening communication between schools and parents, and establishing a preventative dispute resolution mechanism. These efforts are expected to create legal certainty while maintaining a balance between protecting children's rights and protecting the teaching profession.